Inuit medical evacuees and tuberculosis in Hamilton: the makings of a problem - Jonathan, Gire (2017)
In early twentieth century Canada, the tuberculosis (TB) epidemic struck far and wide (Herring, 2007) and its effect was greater on indigenous populations, particularly the Inuit (Public Health Agency of Canada, 2013). In 1906, the Mountain Sanatorium was founded by the Hamilton Health Association (HHA) in an effort to curb the disease (Wilson, 2006) and was designated as a treatment centre for Inuit from the Eastern Arctic. Controlling TB became a movement extensively documented by The Hamilton Spectator – a prime news provider. This research concerns the way in which social problems emerge and the responses they generate. Drawing on the literature on social problems, this thesis examines the HHA’s claims-making activities regarding tuberculosis in 1953-1963 along with The Spectator’s role in helping to define TB as a problem. It examines 1) how the HHA constructed TB as a problem 2) how the HHA understood the problems and solutions of tuberculosis; 3) it ascertains whether the HHA and The Spectator drew from a biomedical model or considered social determinants of health (SDOH) in their control and reportage of the disease; 4) the portrayal and treatment of Inuit patients; 5) the role of legitimacy; and 6) the importance of Pfeffer and Salancik’s resource dependency theory in the Sanatorium’s efforts to survive as an institution. This was executed through a content analysis of the HHA’s annual reports and newspaper articles by The Spectator. The examination of this case through the theory of social problems and resource dependency provides a lens to understand how TB became a problem and why hospitals are more than treatment facilities. Thesis Master of Arts (MA)